EMG activity of finger flexor muscles and grip force following low-dose transcutaneous electrical nerve stimulation in healthy adult subjects. (March 2015) - Kafri, Michal; Zaltsberg, Nir; Dickstein, Ruth
Abstract Somatosensory stimulation modulates cortical and corticospinal excitability and consequently affects motor output. Therefore, low-amplitude transcutaneous electrical nerve stimulation (TENS) has the potential to elicit favorable motor responses. The purpose of the two presented pilot studies was to shed light on TENS parameters that are relevant for the enhancement of two desirable motor outcomes, namely, electromyographic (EMG) activity and contraction strength of the finger flexors and wrist muscles. In 5 and 10 healthy young adults (in Study I and Study II, respectively) TENS was delivered to the volar aspect of the forearm. We manipulated TENS frequency (150 Hz vs. 5 Hz), length of application (10, 20, and 60 min), and side of application (unilateral, right forearm vs. bilateral forearms). EMG amplitude and grip force were measured before (Pre), immediately after (Post), and following 15 min of no stimulation (Study I only). The results indicated that low-frequency bursts of TENS applied to the skin overlying the finger flexor muscles enhance the EMG activity of the finger flexors and grip force. The increase in EMG activity of the flexor muscles was observed after 20 min of stimulation, while grip force was increased only after 1 h. The effects of uni- and bilateral TENS were comparable. These observations allude to a modulatory effect of TENS on the tested motor responses; however, unequivocal conclusions of the findings are hampered by individual differences that affect motor outcomes, such as in level of attention.